Implementasi Model Evaluasi-Refleksi Siklik Dalam Peningkatan Kualitas Pembelajaran Di Madrasah Aliyah - Mandasari, Kiti; N.A, Laila; Adiyono, Adiyono (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Ibn Khaldun Bogor, 2025)
Improving the quality of learning in madrasah requires a systematic approach based on evaluation and reflection. This study aims to analyze the utilization of evaluation and reflection results in improving learning quality at MA Al-Ihsan Tanah Grogot, focusing on the implementation mechanism, the role of school leadership, and its impact on pedagogical practices. Using a qualitative case study approach, data were collected through in-depth interviews with 10 teachers and the madrasah head, participatory observation, and document analysis. The results showed a significant transformation in learning practices, characterized by an increase in the use of digital media from 20% to 65% and a decrease in the pure lecture method from 70% to 30%, which resulted in a 12% increase in the Madrasah Exam average score. Key findings revealed the effectiveness of the cyclic evaluation-reflection model supported by the instructional leadership of the madrasah head, despite the resource constraints. The study concludes that the integration of data-driven evaluation, collaborative reflection and management support can create sustainable learning improvements in a madrasah environment. The implications of this study offer an operational model that can be adapted by other madrasahs with similar characteristics.